2013
DOI: 10.1177/1367877913482323
|View full text |Cite
|
Sign up to set email alerts
|

The politics of reception: ‘Made in China’ and western critique

Abstract: The paper explores some of the reasons for the apparent incommensurability of interpretative attitudes in the consumption of Chinese media products in the West. It also addresses the difficulties faced by existing audience theories in explicating cross--cultural media communication, especially as it applies to the cultural and political divide between China and the West, a phrase I use non--reductively as no more than an abbreviation. The focus of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…More than just an opportunity to demonstrate the Chinese government and people’s competitive spirit and ability to competently run a widely attended and celebrated series of multisport contests, the Olympic Games were treated by the Chinese state as a ‘coming-out party’, or a pivotal site to exhibit the nation-state’s cultural significance and value on the world stage. This strategic promotion of Chinese soft power should be read in the context of the state’s ‘cultural reform’ – a series of policy and industrial measures implemented since the dawn of the new millennium to advance the country’s creative and cultural industries (Keane, 2006; Wang, 2004; Zhang, 2006), and a prelude to a new round of the ‘going out’ campaign launched in 2009 to assert China’s global voice and cultural influence (Chu, 2014). From the detailed attention given to the city’s architecture and landscape to the art performances and large-scale spectacles that were part of the Games, the government mobilized all possible resources to showcase China as cosmopolitan, world-historical, and emanating culture and creativity.…”
mentioning
confidence: 99%
“…More than just an opportunity to demonstrate the Chinese government and people’s competitive spirit and ability to competently run a widely attended and celebrated series of multisport contests, the Olympic Games were treated by the Chinese state as a ‘coming-out party’, or a pivotal site to exhibit the nation-state’s cultural significance and value on the world stage. This strategic promotion of Chinese soft power should be read in the context of the state’s ‘cultural reform’ – a series of policy and industrial measures implemented since the dawn of the new millennium to advance the country’s creative and cultural industries (Keane, 2006; Wang, 2004; Zhang, 2006), and a prelude to a new round of the ‘going out’ campaign launched in 2009 to assert China’s global voice and cultural influence (Chu, 2014). From the detailed attention given to the city’s architecture and landscape to the art performances and large-scale spectacles that were part of the Games, the government mobilized all possible resources to showcase China as cosmopolitan, world-historical, and emanating culture and creativity.…”
mentioning
confidence: 99%
“…Arguments do exist, such as Chu's (2014), that 'Westerners' (of which this Australian audience would be categorised) are unable to read Chinese cinema. Such an argument, however, assumes there is an agreed or culturally homogeneous understanding that Chinese audiences themselves bring to their own national cinema.…”
Section: The Australian Audiencementioning
confidence: 99%
“…If it is a film for the American market, then make it more American, and vice versa. (Chang;cited in Yang, 2012, p. 46) As Dr. Yingchi Chu, Senior Lecturer in Communication and Media Studies at Murdoch University, has shown, cultural differences can lead to different expectations among audiences (Chu, 2014). Chinese audiences tend to be interested in historical drama, while American audiences appreciate contemporary settings.…”
Section: Language Difference and Cultural Differencesmentioning
confidence: 99%